Not the Master of Your Volitional Mind? The Roles of the Right Medial Prefrontal Cortex and Personality Traits in Unconscious Introjections Versus Self-Chosen Goals - Quirin, Markus; Kerber, André; Küstermann, Ekkehard; Radtke, Elise L.; Kazén, Miguel; Konrad, Carsten; Baumann, Nicola; Ryan, Richard M.; Ennis, Michael; Kuhl, Julius (Frontiers in Psychology, 2022)
Humans are unconditionally confronted with social expectations and norms, up to a degree that they or some of them have a hard time recognizing what they actually want. This renders them susceptible for introjection, that is, to unwittingly mistake social expectations about doing relatively unpleasant activities for self-selected goals. Such introjections compromise an individual’s autonomy and mental health and have been shown to be more prevalent in individuals with rumination tendencies and low emotional self-awareness. In this brain imaging study, we draw on a source memory task and found that introjections as indicated by imposed tasks falsely recognized as self-chosen involved the bilateral medial prefrontal cortex (MPFC) and the dorsal anterior cingulate cortex (ACC). Notably, reduced right MPFC activation within this condition correlated with trait scores of rumination and reduced emotional self-awareness, but also introversion. Moreover, correct recognition of tasks as self-chosen involved the right MPFC. Accordingly, the right MPFC may play a role in supporting the maintenance of psychological autonomy and counteract alienation in terms of introjection, which individuals with certain personality traits seem to be prone to. The present research has significant implications for the study of mechanisms underlying autonomous motivation, goal and norm internalization, decision-making, persuasion, education, and clinical conditions such as depression or burnout.